Quantum Learning Method - ., Gunarto (MAGISTRA, 2012)
Gunarto teacher, thinks lhat Quantum Learning Method is one kind of Learning model that using the music melody, or the some kinds in Learning process. The purpose of this writing means to give introduction about the model of Quantum Learning especially for teachers and students, in advanced, hopelycan be used in the learning process, and a! last can raise the students achievements. This writing used a bibliography study, while the data analysis using qualitative data analyze and the data is taken by using reduction system. The result of the study is: the principle of Quantum Learning are, all of them are talking, there is a goal, experiences, acknowledge every single efforts, while the sketch concepts are , To Grow, To Experience, Give a Name, Demonstrate. Riview, and Celebrate (TANDUR). Then, the base is bringing their world to our world and conduct our w>r!d to their world. The conclusion : Quantum Learning can make the Learning process more familiar, decrease the tense situation, relax and having fun. Key W ord : Qtantum Learning and TANDUR.